2015
DOI: 10.1210/jc.2015-1072
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated Retinol Binding Protein 4 Induces Apolipoprotein B Production and Associates With Hypertriglyceridemia

Abstract: Elevated circulating RBP4 concentrations were associated with higher risk of hypertriglyceridemia by inducing the secretion of triglyceride-rich apoB-containing lipoproteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although these findings suggest that there may be subgroups in the population with CVD where elevated retinol concentrations can be particularly harmful, the interaction of retinol with common risk factors of CVD and other diseases should be evaluated in other, preferably healthy cohorts. It would also be useful to assess whether these interactions are present also for RBP4 and retinoic acid in humans, especially considering that data exist that link RBP4 to lipoprotein metabolism (11,33,99,104) and retinoic acid to homocysteine metabolism (105)(106)(107)(108)(109)(110).…”
Section: Serum Retinol -New Hypotheses and Old Challengesmentioning
confidence: 99%
“…Although these findings suggest that there may be subgroups in the population with CVD where elevated retinol concentrations can be particularly harmful, the interaction of retinol with common risk factors of CVD and other diseases should be evaluated in other, preferably healthy cohorts. It would also be useful to assess whether these interactions are present also for RBP4 and retinoic acid in humans, especially considering that data exist that link RBP4 to lipoprotein metabolism (11,33,99,104) and retinoic acid to homocysteine metabolism (105)(106)(107)(108)(109)(110).…”
Section: Serum Retinol -New Hypotheses and Old Challengesmentioning
confidence: 99%
“…Apart from the positive relationship between serum RBP4 and Th17/Treg imbalance, the current study also found that increased serum RBP4 was associated with hyperlipidemia, CVD, and recurrent stroke in stroke patients. Possible explanations are: (1) RBP4 increased the level of blood lipids by inducing apolipoprotein B production ( 28 ). Therefore, elevated serum RBP4 was associated with the occurrence of hyperlipidemia in stroke patients.…”
Section: Discussionmentioning
confidence: 99%